PEMANFAATAN TEPUNG AMPAS KEDELAI DALAM PEMBUATAN KUKIS KACANG TINGGI SERAT DAN PROTEIN - Jessica Wijaya; Maria Goretti Marianti Purwanto; Jane Erika Bernard; Tjandra Pantjajani; Johan Sukweenadhi (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Soybean pulp is a by-product of soy milk production that is a relatively inexpensive source of protein and is recognized for its high fiber content. Gluten-free peanut cookies have been developed using soybean pulp flour. This study aimed to determine the effect of partial replacement of wheat flour with soybean pulp flour (0%, 20%, 50%, and 80%) on peanut cookies’ sensory attributes and physical and chemical properties. Cookies with increased soybean pulp flour substitutions were found to be nutritionally superior (with higher proximate values for protein, fat, crude fiber content, and ash) to whole-wheat cookies (F1). Based on the sensory evaluation, the formulation of 20% soybean pulp flour presented the most likeness for color, flavor, taste, and manual texture. That ratio gave a final product with an average moisture content of 4.1%, ash content of 0.74%, fat content of 10.02%, protein content of 12.93%, crude fiber content of 0.14%, carbohydrate content of 72.21%, texture score of 746 Cn. The higher proportion of Soybean Pulp Flour also resulted in the cookies' darker color and less crunchy texture